Examining the nature of the ultraluminous X-ray source Holmberg II X-1 - Barra, F.; Pinto, C.; Middleton, M.; Di Salvo, T.; Walton, D. J.; Gúrpide, A.; Roberts, T. P. (Astronomy & Astrophysics, 2024)
We present a comprehensive spectral analysis of the ultraluminous X-ray source Holmberg II X-1 using broadband and high-resolution X-ray spectra taken with the XMM-Newton satellite over a period of 19 yr, taking advantage of data from a recent campaign. We tested several models for the broadband spectra, including a double thermal component provided a reasonable description for the continuum between 0.3 and 10 keV and enabled us to constrain the properties of the accretion disc. The luminosity–temperature trends of the inner and outer disc components broadly agree with the expectations for a thin disc, although the exact values of the slopes are slightly sensitive to the adopted model. However, all tested models show L−T trends that deviate from a power law above a bolometric luminosity of about 5×1039 erg s−1 particularly for the hot thermal component associated with the inner accretion flow. Assuming that such deviations are due to the accretion rate exceeding its Eddington limit or, most likely, the super-critical rate, a compact object with a mass of 16–36 M was inferred, specifically, a stellar-mass black hole. The time-averaged (2021) high-resolution spectra present narrow emission lines at 1 keV primarily from Ne ix-x and a very strong at 0.5 keV from N vii, which indicate Ne–N-rich gas with non-solar abundances. This favours a nitrogen-rich donor star, such as a blue or red supergiant, which has escaped from its native stellar cluster characterised by a low-metallicity environment.